Gold/Palladium Alloy for Carbon–Halogen Bond Activation: An Unprecedented Halide Dependence. Issue 12 (30th September 2015) - Dhital, Raghu Nath; Bobuatong, Karan; Ehara, Masahiro; Sakurai, Hidehiro
Abstract: New catalytic activity of gold/palladium alloy nanoclusters (NCs) for carbon–halogen bond activation is demonstrated. In the case of an aryl chloride, the inclusion of gold in a bimetallic catalyst is indispensable to achieve the coupling reactions. Gold has the unique effect of stabilizing palladium, such that Pd 2+ leached from clusters by means of spillover of chloride during oxidative addition. The thus‐formed spillover intermediate further reacts heterogeneously in both Ullmann and Suzuki‐type coupling reactions through a new type of mechanism. In the case of an aryl bromide, Ullmann coupling occurs through the spillover of bromide, similar to that of aryl chloride. However, a significant fraction of palladium also leached, which diminished the Ullmann coupling activity of the aryl bromide and, as a result, the order of reactivity was ArCl>ArBr. With regard to the activation of the C−Br bond towards a Suzuki‐type reaction, the inclusion of a higher gold content in gold/palladium clusters stabilized palladium to prevent the leaching of Pd 2+ from the clusters by means of spillover of bromide. The spillover intermediate reacts heterogeneously with PhB(OH)2, palladium‐rich gold/palladium, or pure palladium clusters; the oxidative addition of ArBr favors the extraction of palladium from the clusters, yielding Pd 2+ intermediates. The extracted intermediates react homogenously (Pd 2+/ Pd 0 catalysis) with PhB(OH)2, which results in the higher selectivity of the cross‐coupling product. An initial step to observe such unprecedented halide dependency, together with the dynamic behavior of palladium on the surface of gold is the oxidative addition of Ar−X. A detailed insight into the first oxidative addition process was also examined by quantum chemical calculations. Abstract : Glittering combination : Unique catalytic activities of gold/palladium alloy for C−Cl and C−Br bond activation are demonstrated. The inclusion of gold has the remarkable effect of stabilizing palladium and allowing Pd 2+ to leach out from the clusters by means of spillover of X (X=Cl or Br) during the oxidative addition of the C−X bond (see figure).